Influence of physical and chemical mutagens on quantitative characters of Vigna mungo (L. Hepper) - L. Mullainathan, C. Thilagavathi (International Multidisciplinary Research Journal, 2011)
<span style="font-size: 10pt; font-family: ";Times New Roman";,";serif";; position: relative; top: 5pt; mso-fareast-font-family: BatangChe; mso-text-raise: -5.0pt; mso-ansi-language: EN-US; mso-fareast-language: KO; mso-bidi-language: AR-SA; mso-no-proof: yes;">Seeds of Urdbean (Vigna mungo (L.) Hepper) Variety Vamban1 was mutagenised with physical and chemical mutagens namely, gamma rays, EMS and dES. In the M1 generation germination percentage, plant growth and yield parameters were adversely affected in the mutagenic treatments and the effects were more pronounced in higher doses indicating almost a linear relationship. The LD50 value was observed in 15 mM of EMS and 25 mM of dES and 60 kR of gamma rays. The increasing dose / concentrations of gamma rays, EMS and dES decreased in phenotypic and yield characters. The decrease quantitative and yield characters have been attributed to the physiological disturbance or chromosomal damage caused to the cells of the plant by the mutagen.Ã‚Â